LncRNA HClnc1 facilitates hepatocellular carcinoma progression by regulating PKM2 signaling and indicates poor survival outcome after hepatectomy - Qian Zhu; Zhengqing Lei; Chang Xu; Zheng Zhang; Zeqian Yu; Zhangjun Cheng; Pengfeng Xiao; Shufeng Li; Weiping Yu; Jiahua Zhou (Cancer Medicine, 2023)
Abstract Aim Long noncoding RNAs (lncRNAs) are key mediators with a wide range of pathophysiological functions, but their role in human hepatocellular carcinoma (HCC) is still unclear. Methods An unbiased microarray study evaluated a novel lncRNA, HClnc1, that is linked to the development of HCC. In vitro cell proliferation assays and an in vivo xenotransplanted HCC tumor model were performed to determine its functions, followed by antisense oligo‐coupled mass spectrometry to identify HClnc1‐interacting proteins. To study relevant signaling pathways, in vitro experiments were performed, including chromatin isolation by RNA purification, RNA immunoprecipitation, luciferase, and RNA pull‐down assay. Results HClnc1 levels were considerably greater in patients with advanced tumor‐node‐metastatic stages, and it was found to be inversely connected to survival rates. Moreover, the proliferative and invasive potential of the HCC cells was attenuated by HClnc1 RNA knockdown in vitro, while HCC tumor growth and metastasis were found to be reduced in vivo. HClnc1 interacted with pyruvate kinase M2 (PKM2) to prevent its degradation and thus facilitated aerobic glycolysis and PKM2‐STAT3 signaling. Conclusions HClnc1 is involved in a novel epigenetic mechanism of HCC tumorigenesis and PKM2 regulation. HClnc1 is not only a more accurate prognostic indicator of HCC but also a potential therapeutic target for HCC treatment.